Analisis Spasial Tingkat Bahaya Bencana Kebakaran Permukiman di Kecamatan Cakung Kota Jakarta Timur - Naomi Betris Simatupang; Sucahyanto Sucahyanto; Sony Nugratama Hijrawadi (Universitas Pendidikan Ganesha, 2026)
The study aims to analyze the level of fire hazard in residential areas in Cakung District spatially using parameters such as frequency of occurrence, economic losses, serious injuries, and fatalities according to BNPB Regulation No. 2 of 2012. The research method combines quantitative descriptive analysis and Geographic Information Systems (GIS) through weighting techniques. The research data was obtained from the DKI Jakarta Regional Disaster Management Agency (BPBD) for the 2019–2023 period. The results show a total of 167 fire incidents with economic losses reaching Rp43.16 billion, 10 serious injuries, and 2 fatalities. The classification of the level of fire hazard in residential areas in Cakung District is that all sub-districts are categorized as moderate. The factors focused on in the analysis of the level of danger according to BNPB Regulation No. 2 of 2012 are non-physical aspects. Population density, building density, and the reach of fire stations contribute to the fire hazard. The resulting hazard map can be a spatial-based mitigation recommendation for policy makers.